A feasible coordination protection strategy for MMC-MTDC systems under DC faults. (September 2017) - Wang, Yizhen; Yuan, Zhichang; Fu, Jiao; Li, Yan; Zhao, Yuming
Highlights: The accurate dc fault current without converter blocking is achieved. The operation characteristics of hybrid dc CBs have been analyzed in details. The strategy has been developed by optimizing parameters of MMC station. Abstract: Modular multilevel converter based multi-terminal HVDC (MMC-MTDC) technology is increasingly adopted as a promising option in the power transmission and distribution fields. However, how to isolate dc fault currents and ensure the continuous operation of the healthy parts of the MMC-MTDC system under dc faults presents a huge challenge. Based on a comprehensive analysis on the dynamic behavior of the dc fault current of a MMC, along with the operation characteristics of hybrid dc circuit breakers (CBs), a protection strategy will be developed. It coordinates the system parameters to ensure the hybrid dc CBs cut off the dc fault current before triggering MMC blocking in bipolar dc faults. The mathematical approximation of the dc fault current without converter blocking is achieved through theoretical analysis and numerical calculation, and the smoothing inductance at the dc side of MMC station has shown a major influence on the dynamic behavior of the dc fault currents. The smoothing inductance can be determined based on the mathematical expression of the dc fault current, as well as the breaking capacity of hybrid dc CBs. Data analysis and simulation are performed based on a three-terminal dc test system to validate the effectiveness of the coordination protection strategy.